White wardah collection and beauty / Aina Furzainie Mat Usop... [et al.] - Mat Usop, Aina Furzainie; Abdul Rahman, Norulhamiza; Azman, Safawati; Al-Yahya, Syarifah Firnaz; Mat Nasir, Umi Fatihah (Faculty of Adminitrative Science & Policy Studies, Universiti Teknologi MARA, 2006)
White Wardah Collection & Beauty is the type of business which involve in image and beauty care for Muslim women. The main business of White Wardah Collection and Beauty is on image care by selling ready made clothes which had been designed according to syariat. "Bertudung" is a must for Muslim women regardless of their age. However there is no factor that limits them from being elegant amd not the main reason for them not to appear stylish. Additionally, wearing "tudung" can be very sweet if we know how to experiment with the colours and to choose the right fashion trend to wear "tudung" with. Therefore, we also provide an image consultancy service which is conduct by our own image consultant. We also provide beauty treatment services as part of our business. In the beauty treatment services, we are more particular on the future brides and needs and after giving birth traditional treatment. Our customers comes from all walks of life, conclusive of corporate women, teenagers, students, future brides and women who had just gave birth and all of them are Muslim. As we can relate, our business in the Islamic entrepreneurship, where Islam encourage the Muslim to venture into businesses that are not in the market yet. To indulge in business is to perform an obligatory duty (fardhu kifayah); unless and until there is an entrepreneur in a community is deemed to be sinful. That is one of the main reasons of why we choose to venture into this business of image and beauty. Qainuqa was the prevailing market place run by the non-Muslim practicing rampant riba (usury) .However profits are merely incidental in the fulfillment of the fardhu kifayah. But that does not imply weakened profit motivation among us, partners. With ubudiah (state of servitude before God) and tauhid (oneness of God), risk taking becomes the guided endeavour; regardless of the outcome of the entrepreneurial Muslim will always be humble and redha (contented with what God has given).